172k views
14 votes
Help please!! 10 points!

Help please!! 10 points!-example-1

1 Answer

7 votes

Answer:

tanG = 2

tanH =
(1)/(2)

Explanation:

The function tangent is the opposite side divided by the adjacent one(SohCahToa).

Relative to angle G, the side with measure 2 is opposite while the wide with measure 1 is adjacent. From this we can set up an equation and substitute:

tan(m<G) =
(opposite)/(adjacent)

tan(m<G) =
(2)/(1) = 2

The same can be done for <H. The opposite side is 1 while the adjacent is 2:

tan(m<H) =
(opposite)/(adjacent)

tan(m<H) =
(1)/(2)

User Daniyalahmad
by
5.3k points